2010 8th IEEE International Conference on Industrial Informatics 2010
DOI: 10.1109/indin.2010.5549626
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the industrial applicability and adoption potential of the AUKOTON model driven control application engineering approach

Abstract: Challenges in software development for automation and control have increased because of various reasons, including the size of applications and competition within the industry. A potential solution could be the use of a model-driven engineering approach to facilitate the development process and design information flow. Despite the wide interests towards modelbased techniques in the automation domain, the authors have not been able to find a complete, tool supported UML based MDE approach, the industrial releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…An approach for model-driven engineering that sufficiently supports the development and implementation of software in aPS needs to provide an automatic generation of executable software, as, e.g., presented by Bonfè et al (2013), Estévez et al (2007), Witsch and Vogel-Heuser (2011) and Yang and Vyatkin (2012). Furthermore, in Vepsalainen et al (2010), it was identified that the modeling of user-defined control logic is required in addition to the application of predefined control blocks. For acceptance of novel concepts, those have to be easily applicable and reproducible for other researchers (Goldberg, 2012).…”
Section: State Of the Artmentioning
confidence: 99%
“…An approach for model-driven engineering that sufficiently supports the development and implementation of software in aPS needs to provide an automatic generation of executable software, as, e.g., presented by Bonfè et al (2013), Estévez et al (2007), Witsch and Vogel-Heuser (2011) and Yang and Vyatkin (2012). Furthermore, in Vepsalainen et al (2010), it was identified that the modeling of user-defined control logic is required in addition to the application of predefined control blocks. For acceptance of novel concepts, those have to be easily applicable and reproducible for other researchers (Goldberg, 2012).…”
Section: State Of the Artmentioning
confidence: 99%
“…when adapting plants to new products and requirements. An approach for the systematic model-based development of production automation systems has been proposed by Vepsäläinen et al [5] with AUKOTON. This approach covers several aspects of an automation system but lacks methods to integrate user-defined control logic [3,6].…”
Section: Model-based Development Of Flexible Automated Production Sysmentioning
confidence: 99%
“…In order to realize such an approach, this paper presents the previous advances of the authors' groups and provides an outlook on a combined approach. In particular, the authors' works towards the model-based development of aPS [4] are discussed in combination with the works towards the model-based code deployment to heterogeneous cyber-physical system architectures [5] and a combined approach is outlined. The remainder of the paper is structured as follows: in Sect.…”
Section: Introductionmentioning
confidence: 99%
“…In one of these works the AUTOKON approach has been developed [11]. The results from the evaluation indicate that industrial practitioners are missing possibilities to specify user-defined or application specific control logic within the AUTOKON approach as well as possibilities to explicitly specify the execution order of Function Blocks [11].…”
Section: Related Workmentioning
confidence: 99%
“…presented by [4], [5], [7], [10]. Furthermore, in [11] it was identified that the modeling of user-defined control logic is required in addition to the application of predefined control blocks.…”
Section: Introductionmentioning
confidence: 99%